Respostas
respondido por:
1
(2+5)•4 ÷ 2•(8-2)
(7)•4 ÷ 2•(6)
28 ÷ 12 ==> : (4/4) = 7/3 ✓
(7)•4 ÷ 2•(6)
28 ÷ 12 ==> : (4/4) = 7/3 ✓
respondido por:
0
Resposta:
Explicação passo-a-passo:
( 2 + 5 ) * 4 : 2 ( ( 8 - 2) =
parenteses
2 + 5 = 7 ***
9 - 2 = 6 = 6 ****
reescrevendo
7 * 4 : 2 * 6 =
multiplicação e divisão faz de acordo com a ordem de colocação
7 * 4 = 28
28 : 2 = 14
14 * 6 = 84 **** resposta
Perguntas similares
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás